ANALYTICAL DEFINITION OF GAS RESERVOIR HYDRODYNAMIC PARAMETERS CHANGES DURING THEIR DEVELOPMENT PROCESS - Акульшин, Олександр Олексійович; Соловйов, В. В.; Кондрат, Олександр Романович; Рой, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
According the results of analytical studies the interrelation of the average diameter of the pores and hashydrodynamic parameters of the wells was determined.